Crafting Design Solutions for Lifelong Learning and Health Promotion in Elderly Communities - Kai-Chieh Lin; Hsiang-Ju Chen; Guan-ying Li (SAGE Open)
Promoting lifelong learning among senior citizens is essential for fostering their confidence and independence. However, the absence of systematic planning and clear definitions of lifelong learning poses challenges in objectively assessing its efficacy. This study aims to establish evaluation criteria and develop a comprehensive health promotion curriculum and evaluation model. The study adopts a mixed methods research approach. In the first phase, semi-structured interviews were conducted to explore the factors influencing motivation and barriers to learning participation. The results identified five primary factors affecting elders’ participation: interpersonal dynamics, adaptation, motivation, interest, and confidence. Based on these findings, the second phase utilized three dimensions—cognitive engagement, physical activity, and social interaction—as the foundation for designing health promotion courses and materials. Appropriate course activities and materials were developed through sensory stimulation and nostalgic experiences to evoke interest. Additionally, a course evaluation scale was constructed based on the analysis of interview results and literature definitions. The Analytic Hierarchy Process (AHP) was employed to establish the hierarchical structure and influence weights for evaluating health promotion courses. Utilizing Analytic Hierarchy Processing (AHP), the evaluation model prioritizes experience and operation & cognition. Essential evaluation metrics include immersiveness, alignment with course objectives, difficulty level, proficiency in operating skills, and fostering creative imagination. To mitigate seniors’ apprehensions regarding failure and engagement, a phased approach to course design is recommended. This iterative process aims to incrementally cultivate confidence and a sense of security among participants, ensuring sustained involvement in the program.